Rubber formulations comprising statistical copolymer comprising vinylbenzocyclobutane

By using benzocyclopropene in the rubber formula, the problem of high cost of hardener in traditional formulas is solved, and cross-linking hardening without hardener is achieved, reducing costs and improving environmental protection.

JP2025059098APending Publication Date: 2025-04-09BRIDGESTONE CORP +1

Patent Information

Application Number
JP2024168553
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-09-27
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Existing rubber formulations require the use of expensive hardeners such as zinc oxide or sulfur, which increases production costs and affects environmental protection.

Method used

Rubber formulations containing vinylbenzocyclobutane (VBCB) statistical copolyacyl can be hardened by self-crosslinking without hardeners.

Benefits of technology

It can achieve hardening of the rubber formula without the use of traditional hardeners, reduce production costs and improve the environmental protection of the formula.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059098000001_ABST
    Figure 2025059098000001_ABST
Patent Text Reader

Abstract

To provide rubber formulations that do not require the addition of curing agents, thereby reducing costs and improving sustainability.SOLUTION: Embodiments of the present disclosure are directed to rubber formulations, wherein the formulations include a statistical copolymer. The statistical copolymer includes a polymerized, crosslinkable reaction product derived from a conjugated diene monomer and vinylbenzocyclobutane. The rubber formulation is substantially free of traditional rubber curing agents.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE Embodiments of the present disclosure relate generally to statistical copolymers comprising vinylbenzocyclobutane, and specifically to rubber compounds comprising statistical copolymers comprising vinylbenzocyclobutane. [Background technology]

[0002] Rubber compounds containing synthetic and / or natural rubber are commonly used in tire applications, such as tire treads. However, curing of the rubber compound may require the addition of curatives such as zinc oxide or sulfur. These curatives may be expensive, and reducing their use may improve the overall sustainability of the rubber compound. Furthermore, the addition of these curatives may require further processing of the rubber compound, which may increase the manufacturing cost of the rubber compound.

[0003] Thus, there is a continuing need for rubber compounds that do not require the addition of curatives, thereby reducing costs and improving sustainability. Summary of the Invention

[0004] The present disclosure is directed to rubber compounds that include statistical copolymers containing vinylbenzocyclobutane, hereinafter referred to as "vinylbenzocyclobutane, VBCB", that can be cured without the use of curatives used in sulfur / zinc-based or peroxide-based crosslinking processes. Specifically, the use of statistical copolymers containing vinylbenzocyclobutane allows for curing without the use of these curatives, since when the vinylbenzocyclobutane is heated, it can react to form crosslinks with other vinylbenzocyclobutane monomers or C-C double bonds present in the statistical copolymer.

[0005] According to one embodiment, a rubber compound is provided. The rubber compound includes a statistical copolymer. The statistical copolymer includes a polymerized crosslinkable reaction product derived from a conjugated diene monomer and vinylbenzocyclobutane. The rubber compound is substantially free of curatives used in sulfur / zinc based crosslinking processes or peroxide based crosslinking processes.

[0006] Additional features and advantages of the embodiments described herein are set forth in the Detailed Description below, and, in part, will be readily apparent to those of ordinary skill in the art from the specification or will be recognized by the practice of the embodiments described herein, including the Detailed Description and Claims below. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a plot of torque (y-axis, in deciNewton meters) versus time (x-axis, in minutes) for an example statistical copolymer with and without the presence of Cu(BF4)2, according to one or more embodiments described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present disclosure is directed to a rubber compound. The rubber compound may include a statistical copolymer. The statistical copolymer may include a polymerized crosslinkable reaction product derived from a conjugated diene monomer and vinylbenzocyclobutane. The rubber compound may be substantially free of curatives used in sulfur / zinc-based crosslinking processes or peroxide-based crosslinking processes.

[0009] This disclosure should not be construed as being limited to the embodiments described herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the subject matter to those skilled in the art.

[0010] definition Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. The terminology used in the present disclosure herein is for the purpose of describing particular embodiments only and is not intended to be limiting.

[0011] Ranges may be expressed herein as from "about" one particular value, and / or to "about" another particular value. When such a range is expressed, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when values ​​are expressed as approximations, by use of the antecedent "about," it will be understood that the particular value forms another embodiment. It will be further understood that the endpoints of each of the ranges are significant both in relation to the other endpoint, and independently of the other endpoint.

[0012] Unless expressly stated otherwise, it is never intended that any method described herein be interpreted as requiring that its steps be performed in a particular order, or as requiring a particular orientation of any physical entity. Thus, where a method claim does not actually recite an order that its steps should be followed, or where a claim relating to any physical entity does not actually recite an order or orientation for individual components, or where it is specifically stated otherwise in the claim or specification that the steps are to be limited to a particular order, or where no particular order or orientation for the components of the physical entity is recited, no order or orientation is ever intended to be inferred in any respect. This applies to any possible implicit criteria for interpretation, including questions of logic regarding the arrangement of steps, operational flow, order of components, or orientation of components; plain meaning derived from grammatical constructions or punctuation; and the number or type of embodiments described herein.

[0013] As used in this specification and the appended claims, the singular forms "a," "an," and "the" are intended to include the plural forms unless the context clearly dictates otherwise. Thus, for example, reference to "a" element includes aspects having two or more such elements unless the context clearly dictates otherwise.

[0014] The term "statistical copolymer", as described herein, refers to a copolymer in which the individual monomer units are arranged according to a statistical distribution along the polymer chain. A statistical copolymer is a copolymer in which the sequential distribution of the monomer units follows known statistical laws. For example, the monomer sequence distribution may follow zero-order (Bernoulli), first-order, second-order, or higher-order Markovian statistics. Kinetically, the basic processes that lead to the formation of statistical sequences of monomer units do not necessarily proceed with equal a priori probability. These processes can lead to various types of sequence distributions, including those in which the arrangement of monomer units tends to alternate, similar units tend to cluster, or show no tendency to order at all. In simple two-component copolymerizations, the nature of this sequence distribution can be indicated by a numerical value that is a function of either the reactivity ratio or the number of trials involved.

[0015] The term "substantially free," as used herein with respect to conventional rubber curatives, refers to an amount of conventional rubber curative that is insufficient to promote curing as measured according to ASTM D2084-19a, such as, for example, 1.0% by weight or less, or 0.9% by weight or less, or 0.8% by weight or less, or 0.7% by weight or less, or 0.6% by weight or less, or 0.5% by weight or less.

[0016] As used herein, the term "phr" refers to parts by weight of a specified component per 100 parts of rubber.

[0017] The number average molecular weight M n , weight average molecular weight M w , and peak molecular weight M pis determined by gel permeation chromatography as detailed in the Examples.

[0018] "MH" refers to "maximum torque" and measures the shear modulus or stiffness value of a fully vulcanized compound, measured according to ASTM D5289.

[0019] "ML" refers to "minimum torque" and measures the value of the vulcanization characteristics (viscosity) of an unvulcanized compound, measured according to ASTM D5289.

[0020] "T90" refers to the time at which the torque increases to ML+90(MH-ML) / 100 dNm and reflects the optimum cure of the compound, as measured according to ASTM D5289.

[0021] "T50" refers to the time at which the torque increases to ML+50(MH-ML) / 100dnM as measured according to ASTM D5289.

[0022] Glass transition temperature T g As described herein, is measured by differential scanning calorimetry.

[0023] The viscoelastic properties described herein, such as loss tangent tan δ at 0° C., 30° C., and 60° C., and storage modulus G′ at −20° C. and −30° C., were measured using temperature sweep tests conducted with an Advanced Rheometric Expansion System (ARES) from TA Instruments.

[0024] The tensile mechanical properties described herein, such as modulus of elasticity at 50% strain M50, modulus of elasticity at 100% strain M100, modulus of elasticity at 200% strain M200, stress at break Tb, and maximum strain Eb, are determined according to ASTM D412, as detailed in the Examples.

[0025] The viscoelastic properties described herein, such as loss tangent tan δ (5%), loss tangent tan δ (10%), and change in storage modulus G' (0.25-14%), were measured by strain sweep testing performed using an Advanced Rheometric Expansion System from TA Instruments.

[0026] As mentioned above, typical rubber curing processes utilize expensive curatives such as zinc oxide and sulfur. The reduction in the use of these curatives can also impact the overall sustainability of the rubber compound. Furthermore, the curatives must typically be added in a separate final stage of mixing at a relatively low temperature to prevent scorching of the rubber. This additional mixing stage can increase the total processing time of the rubber compound.

[0027] Disclosed herein is a rubber compound that alleviates the aforementioned problems. Specifically, the rubber compound disclosed herein includes a statistical copolymer of a conjugated diene monomer and vinylbenzocyclobutane, which results in a rubber compound that does not require the use of zinc oxide or sulfur to cure the rubber compound. The presence of vinylbenzocyclobutane as part of the statistical copolymer allows crosslinks to occur between polymer chains, and the statistical distribution of vinylbenzocyclobutane along the polymer chains promotes a uniform distribution of crosslinks with a higher crosslink density. This crosslinking allows the rubber compound to be cured without the use of curatives such as zinc oxide and sulfur, thereby reducing costs and improving the sustainability of the rubber compound.

[0028] Statistical Copolymer The statistical copolymers disclosed herein can be generally described as comprising a conjugated diene and vinylbenzocyclobutane.

[0029] The statistical copolymer includes vinylbenzocyclobutane. Without being bound by theory, it is believed that the VBCB monomer units in a polymer chain may form crosslinks with other VBCB monomer units on other polymer chains and may also form crosslinks with unsaturation in the polymer backbone of other polymer chains. These crosslinks can provide the statistical copolymer with desirable mechanical properties when the statistical copolymer is cured. Furthermore, it is believed that the presence of vinylbenzocyclobutane can cure rubber compounds without the use of curatives such as zinc oxide and sulfur. In embodiments, the statistical copolymer can be a polymerized crosslinkable reaction product derived from conjugated diene monomers and VBCB.

[0030] In embodiments, the statistical copolymer may comprise VBCB in an amount of about 0.02 wt% or more, about 0.1 wt% or more, about 0.25 wt% or more, about 0.5 wt% or more, about 0.75 wt% or more, or even about 1.0 wt% or more, based on the total weight of the statistical copolymer. In embodiments, the statistical copolymer may comprise VBCB in an amount of about 2.0 wt% or less, about 1.75 wt% or less, about 1.5 wt% or less, or even about 1.25 wt% or less, based on the total weight of the statistical copolymer. In embodiments, the statistical copolymer comprises from about 0.02 wt % to about 2.0 wt %, from about 0.02 wt % to about 1.75 wt %, from about 0.02 wt % to about 1.5 wt %, from about 0.02 wt % to about 1.25 wt %, from about 0.1 wt % to about 2.0 wt %, from about 0.1 wt % to about 1.75 wt %, from about 0.1 wt % to about 1.5 wt %, from about 0.1 wt % to about 1.25 wt %, from about 0.25 wt % to about 2.0 wt %, from about 0.25 wt % to about 1.75 wt %, from about 0.25 wt % to about 1.5 wt %, from about 0.25 wt % to about 1.25 wt %, or from about 0.5 wt %, based on the total weight of the statistical copolymer. % to about 2.0 wt%, about 0.5 wt% to about 1.75 wt%, about 0.5 wt% to about 1.5 wt%, about 0.5 wt% to about 1.25 wt%, about 0.75 wt% to about 2.0 wt%, about 0.75 wt% to about 1.75 wt%, about 0.75 wt% to about 1.5 wt%, about 0.75 wt% to about 1.25 wt%, about 1.0 wt% to about 2.0 wt%, about 1.0 wt% to about 1.75 wt%, about 1.0 wt% to about 1.5 wt%, or even about 1.0 wt% to about 1.25 wt%, or any and all subranges formed from any of these endpoints. Without being bound by theory, it is believed that statistical copolymers containing less than 0.02 wt% VBCB may not have the desired crosslink density and distribution after curing. It is also believed that amounts of VBCB greater than 2.0 weight percent can adversely affect the tensile properties of the cured rubber compound, such as the elongation of the rubber compound.

[0031] In embodiments, the polymer may contain 1 to 15 VBCB monomer units per polymer chain. In embodiments, the polymer may contain 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, or even 7 or more VBCB monomer units per polymer chain. In embodiments, the polymer may contain 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, or even 9 or less VBCB monomer units per polymer chain. In embodiments, the polymer may have 1-15, 1-14, 1-13, 1-12, 1-11, 1-10, 1-9, 2-15, 2-14, 2-13, 2-12, 2-11, 2-10, 2-9, 3-15, 3-14, 3-13, 3-12, 3-11, 3-10, 3-9, 4-15, 4-14, 4-13, 4-12, 4-11, 4-10, 4-15, 4-14, 4-13, 4-12, 4-11, 4-10, 4-15, 4-16, 4-17, 4-18, 4-20, 4-21, 4-22, 4-23, 4-24, 4-25, 4-26, 4-27, 4-28, 4-29, 4-30, 4-31, 4-32, 4-33, 4-34, 4-35, 4-36, 4-37, 4-38, 4-39, 4-40, 4-41, 4-42, 4-43, 4-44, 4-45, 4-46, 4-47, 4-48, 4-49, 4-50, 4-51, 4-52, 4-53, 4-54, 4-55, 4-56, 4-57, 4-58, 4-59, 4-60, 4-61, 4-62, 4-63, 4-64, 4-65, 4-70, 4- from 7 to 9, 5 to 15, 5 to 14, 5 to 13, 5 to 12, 5 to 11, 5 to 10, 5 to 9, 6 to 15, 6 to 14, 6 to 13, 6 to 12, 6 to 11, 6 to 10, 6 to 9, 7 to 15, 7 to 14, 7 to 13, 7 to 12, 7 to 11, 7 to 10, or even 7 to 9, or any and all subranges formed from any of these endpoints of VBCB monomer units.

[0032] In embodiments, the polymer may have at least one VBCB monomer unit at a terminal end of the polymer chain. In embodiments, the polymer may have at least two, at least three, or even at least four VBCB monomer units at a terminal end of the polymer chain. In embodiments, the polymer may have 1-4, 1-3, 1-2, 2-4, 2-3, 3-4 VBCB monomer units at a terminal end of the polymer chain, or any and all subranges formed from any of these endpoints.

[0033] In embodiments, about 50% or more of the polymer chains in the polymer may have 0.5 to 3 VBCB monomer units on the polymer terminals. In embodiments, about 55% or more, about 60% or more, about 65% or more, about 70% or more, about 75% or more, about 80% or more, about 85% or more, or even about 90% or more of the polymer chains may have 0.5 to 3 VBCB monomer units on the polymer terminals. In embodiments, about 50% or more of the polymer chains in the polymer may have 0.5-3, 0.5-2.5, 0.5-2, 0.5-1.5, 0.5-1, 1-3, 1-2.5, 1-2, 1-1.5, 1.5-3, 1.5-2.5, 1.5-2, 2-3, 2-2.5, 2.5-3, or any and all subranges formed from any of these endpoints, VBCB monomer units on a terminal end of the polymer. In such embodiments, the remainder of the VBCB monomer units may be statistically distributed throughout the polymer chains.

[0034] The statistical copolymer disclosed herein comprises a conjugated diene. Without being bound by theory, it is believed that the VBCB monomer unit can form crosslinks with the carbon-carbon double bonds of the conjugated diene monomer unit. This can allow for increased crosslink density since the VBCB monomer unit can form more crosslinks compared to polymers that do not comprise conjugated diene monomer units.

[0035] In embodiments, the conjugated diene monomer may be selected from the group consisting of 1,3-butadiene, isoprene, 1,3-pentadiene, 1,3-hexadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 2-methyl-1,3-pentadiene, 3-methyl-1,3-pentadiene, 4-methyl-1,3-pentadiene, 2,4-hexadiene, 1,3-cyclopentadiene, 1,3-cyclohexadiene, 1,3-cycloheptadiene, 1,3-cyclooctadiene, and combinations thereof. In embodiments, the conjugated diene monomer may be 1,3-butadiene.

[0036] In embodiments, the statistical copolymer may comprise from about 50% to about 99% by weight of the conjugated diene monomer, based on the total weight of the statistical copolymer. In embodiments, the statistical copolymer may comprise conjugated diene monomer in an amount of about 50% or more, about 55% or more, about 60% or more, or even about 65% or more by weight, based on the total weight of the statistical copolymer. In embodiments, the statistical copolymer may comprise conjugated diene monomer in an amount of about 99% or less, about 95% or less, about 90% or less, about 85% or less, or even about 80% or less by weight, based on the total weight of the statistical copolymer. In embodiments, the statistical copolymer comprises from about 50% to about 99% by weight, from about 50% to about 95% by weight, from about 50% to about 90% by weight, from about 50% to about 85% by weight, from about 50% to about 80% by weight, from about 55% to about 99% by weight, from about 55% to about 90% by weight, from about 55% to about 85% by weight, from about 55% to about 80% by weight, from about 60% to about 9 ... % to about 95% by weight, about 60% to about 90% by weight, about 60% to about 85% by weight, about 60% to about 80% by weight, about 65% to about 99% by weight, about 65% to about 95% by weight, about 65% to about 90% by weight, about 65% to about 85% by weight, or even about 65% to about 80% by weight, or any and all subranges formed from any of these endpoints.

[0037] In some embodiments, the statistical copolymer may be a polymerized crosslinkable reaction product derived from a conjugated diene monomer, a vinyl aromatic monomer, and VBCB. Without being bound by theory, it is believed that the presence of the vinyl aromatic monomer may increase the glass transition of the polymer compared to a polymer that does not contain the vinyl aromatic monomer. Increasing the glass transition temperature of the polymer may improve the wet and dry traction of tires made using a rubber compound containing the polymer.

[0038] In embodiments, the vinyl aromatic monomer may be selected from the group consisting of styrene, alpha-methylstyrene, p-methylstyrene, o-methylstyrene, p-butylstyrene, vinylnaphthalene, p-tertbutylstyrene, 4-vinylbiphenyl, 2-vinylnaphthalene, 9-vinylanthracene, vinylcatechol, and combinations thereof. In embodiments, the vinyl aromatic monomer may be styrene.

[0039] In embodiments, the statistical copolymer may comprise from about 5% to about 50% by weight of the vinyl aromatic monomer, based on the total weight of the statistical copolymer. In embodiments, the statistical copolymer may comprise at least about 5% by weight, at least about 10% by weight, at least about 15% by weight, or even at least about 20% by weight of the vinyl aromatic monomer, based on the total weight of the statistical copolymer. In embodiments, the statistical copolymer may comprise at most about 50% by weight, at most about 45% by weight, at most about 40% by weight, at most about 35% by weight, or even at most about 30% by weight of the vinyl aromatic monomer, based on the total weight of the statistical copolymer. In embodiments, the statistical copolymer comprises from about 5% to about 50% by weight, from about 5% to about 45% by weight, from about 5% to about 40% by weight, from about 5% to about 35% by weight, from about 5% to about 30% by weight, from about 10% to about 50% by weight, from about 10% to about 45% by weight, from about 10% to about 40% by weight, from about 10% to about 35% by weight, from about 10% to about 30% by weight, from about 15% to about 50% by weight, based on the total weight of the statistical copolymer. The vinyl aromatic monomer may be present in an amount of about 15% to about 45% by weight, about 15% to about 40% by weight, about 15% to about 35% by weight, about 15% to about 30% by weight, about 20% to about 50% by weight, about 20% to about 45% by weight, about 20% to about 40% by weight, about 20% to about 35% by weight, or even about 20% to about 30% by weight, or any and all subranges formed from any of these endpoints.

[0040] In embodiments, the statistical copolymer may have a conjugated diene monomer, a vinyl aromatic monomer, or a combination thereof incorporated between VBCB monomer units of a weight average molecular weight of about 10,000 g / mol to about 50,000 g / mol. In embodiments, the statistical copolymer may have a conjugated diene monomer, a vinyl aromatic monomer, or a combination thereof incorporated between VBCB monomer units of a weight average molecular weight of about 10,000 g / mol or more, about 15,000 g / mol or more, about 20,000 g / mol or more, or even about 25,000 g / mol or more. In embodiments, the statistical copolymer may have a conjugated diene monomer, a vinyl aromatic monomer, or a combination thereof incorporated between VBCB monomer units of a weight average molecular weight of about 50,000 g / mol or less, about 45,000 g / mol or less, about 40,000 g / mol or less, or even about 35,000 g / mol or less. In embodiments, the statistical copolymer may be from about 10,000 g / mol to about 50,000 g / mol, from about 10,000 g / mol to about 45,000 g / mol, from about 10,000 g / mol to about 40,000 g / mol, from about 10,000 g / mol to about 35,000 g / mol, from about 15,000 g / mol to about 50,000 g / mol, from about 15,000 g / mol to about 45,000 g / mol, from about 15,000 g / mol to about 40,000 g / mol, from about 15,000 g / mol to about 35,000 g / mol, from about 20,000 g / mol to about 50,000 g / mol, from about 20,000 g / mol to about 45,0 00 g / mol, about 20,000 g / mol to about 40,000 g / mol, about 20,000 g / mol to about 35,000 g / mol, about 25,000 g / mol to about 50,000 g / mol, about 25,000 g / mol to about 45,000 g / mol, about 25,000 g / mol to about 40,000 g / mol, or even about 25,000 g / mol to about 35,000 g / mol, or any and all subranges formed from any of these endpoints.Without being bound by theory, it is believed that if the weight average molecular weight of the conjugated diene monomer incorporated between the VBCB monomer units, the incorporated vinyl aromatic monomer, or a combination thereof is less than about 10,000 g / mol, the rubber compound may cure too densely, which may adversely affect the elongation of the cured rubber. It is also believed that if the weight average molecular weight of the conjugated diene monomer incorporated between the VBCB monomer units, the incorporated vinyl aromatic monomer, or a combination thereof is greater than about 50,000 g / mol, the rubber compound may lack the desired crosslink density.

[0041] In some embodiments, the statistical copolymer has a molecular weight of about 1.0×10 5 g / mol ~ approx. 2.0×10 6 Weight average molecular weight M in g / mol w In embodiments, the statistical copolymer may have a molecular weight of about 1.0×10 5 g / mol or more, approximately 2.5×10 5 g / mol or more, approximately 5.0×10 5 g / mol or more, or even about 7.5×10 5 Weight average molecular weight M in g / mol or more w In embodiments, the statistical copolymer may have a molecular weight of about 2.0×10 6 g / mol or less, approximately 1.75×10 6 g / mol or less, approximately 1.5×10 6 g / mol or less, or even about 1.25×10 6 Weight average molecular weight M in g / mol or less w In embodiments, the statistical copolymer may have a molecular weight of about 1.0×10 5 g / mol ~ approx. 2.0×10 6 g / mol, approximately 1.0×10 5 g / mol ~ approx. 1.75×10 6 g / mol, approximately 1.0×10 5 g / mol ~ approx. 1.5×10 6 g / mol, approximately 1.0×10 5 g / mol ~ approx. 1.25×10 6 g / mol, approximately 2.5×10 5g / mol ~ approx. 2.0×10 6 g / mol, approximately 2.5×10 6 g / mol ~ approx. 1.75×10 6 g / mol, approximately 2.5×10 5 g / mol ~ approx. 1.5×10 6 g / mol, approximately 2.5×10 5 g / mol ~ approx. 1.25×10 6 g / mol, approximately 5.0×10 5 g / mol ~ approx. 2.0×10 6 g / mol, approximately 5.0×10 5 g / mol ~ approx. 1.75×10 6 g / mol, approximately 5.0×10 5 g / mol ~ approx. 1.5×10 6 g / mol, approximately 5.0×10 5 g / mol ~ approx. 1.25×10 6 g / mol, approximately 7.5×10 5 g / mol ~ approx. 2.0×10 6 g / mol, approximately 7.5×10 5 g / mol ~ approx. 1.75×10 6 g / mol, approximately 7.5×10 5 g / mol ~ approx. 1.5×10 6 g / mol, or even about 7.5×10 5 g / mol ~ approx. 1.25×10 6 The weight average molecular weight M of g / mol, or any and all subranges formed from any of these endpoints. w Without being bound by theory, the molecular weight may be about 1.0×10 5 Statistical copolymers with weight average molecular weights below 1.0×10 g / mol have an increased risk of cold flow. 5 g / mol ~ approx. 2.0×10 6 It is believed that a statistical copolymer having a weight average molecular weight of about 2.0×10 6 A statistical copolymer having a weight average molecular weight of more than about 1.0×10 5 g / mol ~ approx. 2.0×10 6It is believed that they may be more difficult to process than statistical copolymers having weight average molecular weights of g / mol.

[0042] In some embodiments, the copolymer has a molecular weight of about 1.0×10 5 g / mol ~ approx. 2.0×10 6 Number average molecular weight M in g / mol n In embodiments, the copolymer may have a molecular weight of about 1.0×10 5 g / mol or more, approximately 2.5×10 5 g / mol or more, approximately 5.0×10 5 g / mol or more, or even about 7.5×10 5 Number average molecular weight M in g / mol or more n In embodiments, the copolymer may have a molecular weight of about 2.0×10 6 g / mol or less, approximately 1.75×10 6 g / mol or less, approximately 1.5×10 6 g / mol or less, or even about 1.25×10 6 Number average molecular weight M in g / mol n In embodiments, the copolymer may have a molecular weight of about 1.0×10 5 g / mol ~ approx. 2.0×10 6 g / mol, approximately 1.0×10 5 g / mol ~ approx. 1.75×10 6 g / mol, approximately 1.0×10 5 g / mol ~ approx. 1.5×10 6 g / mol, approximately 1.0×10 5 g / mol ~ approx. 1.25×10 6 g / mol, approximately 2.5×10 5 g / mol ~ approx. 2.0×10 6 g / mol, approximately 2.5×10 6 g / mol ~ approx. 1.75×10 6 g / mol, approximately 2.5×10 5 g / mol ~ approx. 1.5×10 6 g / mol, approximately 2.5×10 5 g / mol ~ approx. 1.25×10 6 g / mol, approximately 5.0×10 5 g / mol ~ approx. 2.0×10 6g / mol, approximately 5.0×10 5 g / mol ~ approx. 1.75×10 6 g / mol, approximately 5.0×10 5 g / mol ~ approx. 1.5×10 6 g / mol, approximately 5.0×10 5 g / mol ~ approx. 1.25×10 6 g / mol, approximately 7.5×10 5 g / mol ~ approx. 2.0×10 6 g / mol, approximately 7.5×10 5 g / mol ~ approx. 1.75×10 6 g / mol, approximately 7.5×10 5 g / mol ~ approx. 1.5×10 6 g / mol, or even about 7.5×10 5 g / mol ~ approx. 1.25×10 6 The number average molecular weight M of g / mol, or any and all subranges formed from any of these endpoints. n

[0043]

[0043] In some embodiments, the copolymer has a molecular weight of about 1.0×10 5 g / mol ~ approx. 2.0×10 6 Peak molecular weight M in g / mol p In embodiments, the copolymer may have a molecular weight of about 1.0×10 5 g / mol or more, approximately 2.5×10 5 g / mol or more, approximately 5.0×10 5 g / mol or more, or even about 7.5×10 5 Peak molecular weight M in g / mol or more p In embodiments, the copolymer may have a molecular weight of about 2.0×10 6 g / mol or less, approximately 1.75×10 6 g / mol or less, approximately 1.5×10 6 g / mol or less, or even about 1.25×10 6 Peak molecular weight M in g / mol or less p In embodiments, the copolymer may have a molecular weight of about 1.0×10 5 g / mol ~ approx. 2.0×10 6 g / mol, approximately 1.0×10 5g / mol ~ approx. 1.75×10 6 g / mol, approximately 1.0×10 5 g / mol ~ approx. 1.5×10 6 g / mol, approximately 1.0×10 5 g / mol ~ approx. 1.25×10 6 g / mol, approximately 2.5×10 5 g / mol ~ approx. 2.0×10 6 g / mol, approximately 2.5×10 6 g / mol ~ approx. 1.75×10 6 g / mol, approximately 2.5×10 5 g / mol ~ approx. 1.5×10 6 g / mol, approximately 2.5×10 5 g / mol ~ approx. 1.25×10 6 g / mol, approximately 5.0×10 5 g / mol ~ approx. 2.0×10 6 g / mol, approximately 5.0×10 5 g / mol ~ approx. 1.75×10 6 g / mol, approximately 5.0×10 5 g / mol ~ approx. 1.5×10 6 g / mol, approximately 5.0×10 5 g / mol ~ approx. 1.25×10 6 g / mol, approximately 7.5×10 5 g / mol ~ approx. 2.0×10 6 g / mol, approximately 7.5×10 5 g / mol ~ approx. 1.75×10 6 g / mol, approximately 7.5×10 5 g / mol ~ approx. 1.5×10 6 g / mol, or even about 7.5×10 5 g / mol ~ approx. 1.25×10 6 g / mol, or any and all subranges formed from either of these endpoints, p

[0043]

[0044] In embodiments, statistical copolymers can have a polydispersity (PDI) of 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less, or even 1.1 or less.

[0045] In embodiments, the statistical copolymer has a glass transition temperature T of about -100°C to about -20°C. g In embodiments, the statistical copolymer may have a glass transition temperature T of -100°C or higher, -90°C or higher, -80°C or higher, or even -70°C or higher. g In embodiments, the statistical copolymer may have a glass transition temperature T g In embodiments, the statistical copolymer may have a glass transition temperature T of about -100°C to about -20°C, about -100°C to about -30°C, about -100°C to about -40°C, about -100 to about -50°C, about -90°C to about -20°C, about -90°C to about -30°C, about -90°C to about -40°C, about -90°C to about -50°C, about -80°C to about -20°C, about -80°C to about -30°C, about -80°C to about -40°C, about -80°C to about -50°C, about -70°C to about -20°C, about -70°C to about -30°C, about -70°C to about -40°C, or even about -70°C to about -50°C, or any and all subranges formed from any of these endpoints. g Without being bound by theory, it is believed that a glass transition temperature above about -20°C may adversely affect the snow and rolling resistance performance of a tire tread incorporating the statistical copolymer.

[0046] In embodiments, the rubber component of the rubber compound may comprise the statistical copolymer in an amount of about 20 phr or more, about 30 phr or more, about 40 phr or more, or even about 50 phr or more, based on the total weight of the rubber components. In embodiments, the rubber component may comprise the statistical copolymer in an amount of about 100 phr or less, about 90 phr or less, about 80 phr or less, or even about 70 phr or less, based on the total weight of the rubber components. In embodiments, the rubber component may comprise a statistical copolymer in an amount of from about 20 phr to about 100 phr, from about 20 phr to about 90 phr, from about 20 phr to about 80 phr, from about 20 phr to about 70 phr, from about 30 phr to about 100 phr, from about 30 phr to about 90 phr, from about 30 phr to about 80 phr, from about 30 phr to about 70 phr, from about 40 phr to about 100 phr, from about 40 phr to about 90 phr, from about 40 phr to about 80 phr, from about 40 phr to about 70 phr, from about 50 phr to about 100 phr, from about 50 phr to about 90 phr, from about 50 phr to about 80 phr, or even from about 50 phr to about 70 phr, or any and all subranges formed from any of these endpoints, based on the total weight of the rubber component.

[0047] Practice of the invention also advantageously provides a method for producing tire components from a cured rubber matrix having a relatively high content of sustainable constituents, including recycled materials, naturally occurring materials, and / or materials synthesized from biosynthetic or bio-based sources. For example, a tire or tire component of the invention may include greater than 40% by weight, and in other embodiments greater than 50% by weight, and in other embodiments greater than 60% by weight of sustainable materials. In these or other embodiments, the tire or tire component includes from about 40 to about 90% by weight, and in other embodiments from about 45 to about 85% by weight, and in other embodiments from about 50 to about 80% by weight of sustainable materials. The cured rubber matrix having the filler dispersed therein may include greater than 40% by weight, or greater than 50% by weight, or greater than 60% by weight, or greater than 70% by weight, or greater than 80% by weight, or greater than 90% by weight, or greater than 99% by weight of a statistical copolymer.

[0048] Filler The rubber composition of the present invention includes fillers such as inorganic and organic fillers. Examples of organic fillers include carbon black and starch. Examples of inorganic fillers include silica, aluminum hydroxide, magnesium hydroxide, mica, talc (hydrated magnesium silicate), and clay (hydrated aluminum silicate). In certain embodiments, mixtures of different fillers may be used to advantage.

[0049] The amount of total filler used in the rubber composition may be up to about 150 parts by weight per 100 parts by weight of rubber (phr), with from about 30 to about 125 phr, or from about 40 to about 110 phr being typical. In certain embodiments, the total filler content is greater than about 100 phr. In other embodiments, the total filler content is from about 50 to about 100 phr, and in further embodiments, from about 55 to about 95 phr.

[0050] Conventional carbon black generally known in the art can be used. In one or more embodiments, carbon black includes furnace black, channel black, and lamp black. More specific examples of carbon black include super abrasion furnace black, medium super abrasion furnace black, high abrasion furnace black, high speed extrusion furnace black, fine furnace black, semi-reinforced furnace black, medium processing channel black, hard processing channel black, conductive channel black, and acetylene black.

[0051] In certain embodiments, the carbon black has a surface area (EMSA) of at least 20 m 2 / g, in other embodiments, at least 35m 2The surface area may be expressed in terms of gram per gram, and the surface area value may be determined using the cetyltrimethylammonium bromide (CTAB) technique per ASTM standard D-1765. The carbon black may be in pelletized or non-pelletized flocculent form. The preferred form of the carbon black may depend on the type of mixing equipment used to mix the rubber compound.

[0052] In one or more embodiments, the carbon black may utilize recycled materials. Such recycled materials may include reclaimed or recycled vulcanized rubber, which is typically reclaimed from manufactured articles such as pneumatic tires, industrial conveyor belts, power transmission belts, and rubber hoses. Recycled carbon black is obtained by pyrolysis processes or other methods known for obtaining recycled carbon black. In one aspect, recycled carbon black may be formed from the incomplete combustion of recycled rubber feedstock or rubber articles. In another aspect, recycled carbon black may be formed from the incomplete combustion of oil-containing feedstock resulting from tire pyrolysis processes. The carbon black used in the preparation of the vulcanizable elastomeric composition may be in pelletized form or non-pelletized flocculent.

[0053] The amount of total filler used in the rubber composition may be up to about 75 parts by weight per 100 parts by weight rubber (phr), with from about 5 to about 60 phr, or from about 10 to about 55 phr being typical.

[0054] The rubber composition may further include a filler in the form of one or more reclaimed rubbers in particulate form. Recycled particulate rubber is typically broken down and reclaimed (or recycled) by any of a number of processes, which may include physical break down, grinding, chemical break down, devulcanization, cryogenic grinding, combinations thereof, and the like. The term "recycled particulate rubber" may relate to both vulcanized and devulcanized rubber, with devulcanized recycled or recycled rubber (reclaimed rubber) relating to rubber that has been vulcanized, ground into particles, and may have been further subjected to substantial or partial devulcanization. In one example, the recycled particulate rubber used in the rubber composition is essentially free of recycled rubber resulting from devulcanization. In situations where the vulcanized rubber contains wire or woven fiber reinforcement, such wire or fiber reinforcement may be removed by any suitable process, such as magnetic separation, air suction, and / or air flotation steps. In certain embodiments, "recycled particulate rubber" includes cured, i.e., vulcanized (crosslinked), rubber that has been ground or powdered into particulate matter having an average particle size as discussed below.

[0055] Commercially available silicas that may be used in the present invention include Hi-Sil™ 215, Hi-Sil™ 233, and Hi-Sil™ 190 (PPG Industries, Inc., Pittsburgh, Pa.). Other suppliers of commercially available silicas include Grace Davison (Baltimore, Md.), Degussa Corp. (Parsippany, NJ), Rhodia Silica Systems (Cranbury, NJ), and JM Huber Corp. (Edison, NJ). Such silicas may be considered sustainable materials. Other sustainable silicas include those derived from rice husk ash.

[0056] In one or more embodiments, silica can be characterized by its surface area, which is a measure of its reinforcing properties. The Brunauer, Emmet and Teller ("BET") method (described in J. Am. Chem. Soc., 1939, vol. 60, 2 p. 309-319) is an accepted method for determining surface area. The BET surface area of ​​silica is generally about 450 m 2 / g. A useful range of surface area is from about 32 to about 400 m 2 / g, about 100~250m 2 / g, about 130~240m 2 / g, and about 170 to about 220 m 2 In certain embodiments, the silica has a molecular weight of 190 to about 280 m / g. 2 The pH of the silica generally ranges from about 5 to about 7, or slightly greater than 7, or in other embodiments, from about 5.5 to about 6.8.

[0057] In one or more embodiments, when silica is used as a filler (alone or in combination with other fillers), a coupling agent and / or shielding agent may be added to the rubber composition during mixing to enhance the interaction of the silica with the elastomer. Useful coupling agents and shielding agents are disclosed in U.S. Patents 3,842,111, 3,873,489, 3,978,103, 3,997,581, 4,002,594, 5,580,919, 5,583,245, 5,663,396, 5,674,932, 5,71 ... Nos. 6,684,171, 5,684,172, 5,696,197, 6,608,145, 6,667,362, 6,579,949, 6,590,017, 6,525,118, 6,342,552, and 6,683,135, which are incorporated herein by reference.

[0058] The amount of silica used in the rubber composition can be from about 1 to about 150 phr, or in other embodiments from about 5 to about 130 phr. The useful upper range is limited by the high viscosity imparted by the silica. In certain embodiments, the silica used in the rubber composition is derived exclusively from rice husk ash, and in other embodiments, the rubber composition does not include silica from a non-rice husk ash derived process. When silica is used with carbon black, the amount of silica or carbon black, respectively, can be as low as about 1 phr. Generally, the amount of binder and shielding agent ranges from about 4% to about 20% by weight, based on the weight of the silica used. In one or more embodiments in which carbon black and silica are used in combination as fillers, the weight ratio, or silica to total filler, can be from about 5% to about 99% by weight of the total filler, in other embodiments from about 10% to about 90% by weight of the total filler, or in yet other embodiments from about 50% to about 85% by weight of the total filler. In certain embodiments, the silica and carbon black fillers used in the rubber composition are selected from the group consisting of sustainable pyrolytic carbon black and / or rice husk ash derived silica.

[0059] A number of rubber curing agents (also called vulcanizing agents) may be used, including sulfur or peroxide based cure systems. Curing agents are described in Kirk-Othmer, ENCYCLOPEDIA OF CHEMICAL TECHNOLOGY, Vol. 20, pgs. 365-468, (3rd Ed. 1982), especially Vulcanization Agents and Auxiliary Materials, pgs. 390-402, and AY Coran, Vulcanization, ENCYCLOPEDIA OF POLYMER SCIENCE AND ENGINEERING, (2nd Ed. 1989), which are incorporated herein by reference. Vulcanizing agents may be used alone or in combination.

[0060] Other ingredients typically used in rubber compounding may also be added to the rubber composition, including accelerators, accelerator activators, oils, plasticizers, waxes, antiscorch agents, processing aids, zinc oxide, tackifying resins, reinforcing resins, fatty acids such as stearic acid, peptizers, and antidegradants such as antioxidants and antiozonants.

[0061] Regarding oil, sustainable oils may be used, including vegetable-based oils and bio-based oils. Vegetable-based oils may include vegetable triglycerides. Exemplary oils include, but are not limited to, palm oil, soybean oil (also referred to herein as soybean oil), rapeseed oil, sunflower seed, peanut oil, cottonseed oil, oil produced from palm kernel, coconut oil, olive oil, corn oil, grape seed oil, hemp oil, linseed oil, rice oil, safflower oil, sesame oil, mustard oil, and flaxseed oil. Other examples include oils derived from nuts, such as oils obtained from beech, cashew nuts, mongo nuts, macadamia nuts, pine nuts, hazel nuts, chestnuts, acorns, almonds, pecans, pistachios, walnuts, or Brazil nuts. As will be appreciated by those of skill in the art, these oils may be produced by any suitable process, such as mechanical extraction (e.g., using an oil mill), chemical extraction (e.g., using solvents such as hexane or carbon dioxide), pressure extraction, distillation, percolation, disintegration, refining, purification, hydrogenation, sparging, and the like.

[0062] Bio-based oils, also referred to as bio-oils, can include oils produced by recombinant cells. For example, recombinantly produced bio-oils can be produced using selected strains of algae cells that are fed a sugar (e.g., sucrose) and fermented to produce a bio-oil with a selected profile. Upon sufficient growth or fermentation, the bio-oil is separated from the cells and collected.

[0063] Generally, the rubber compositions of the present invention may contain from about 1 to about 70 parts by weight, or in other embodiments from about 5 to about 50 parts by weight, of total oil per 100 parts by weight of rubber. The amount of sustainable oil may be from about 1% to about 99% by weight, or in other embodiments from about 20% to about 80% by weight, based on the total weight of oil present.

[0064] With regard to waxes, the rubber composition may include one or more sustainable waxes, including natural waxes, which may include carnauba wax, candelilla wax (e.g., extracted from candelilla flowers), rice wax (e.g., isolated from rice bran oil), and Japan wax (e.g., extracted from Japanese laurel).

[0065] Generally, the rubber composition of the present invention comprises from about 1 to about 20 parts by weight, or in other embodiments from about 2 to about 15 parts by weight, of total wax per 100 parts by weight of rubber. The amount of sustainable wax may be from about 1% to about 99% by weight, or in other embodiments from about 20% to about 80% by weight of total wax, based on the total weight of waxes included. In certain embodiments, the rubber composition comprises only sustainable waxes.

[0066] In embodiments, the rubber formulation may include a silane as a coupling agent. In embodiments, the rubber formulation may include from about 1 phr to about 20 phr of the silane. In embodiments, the amount of silane in the rubber formulation may be about 1 phr or more, about 2 phr or more, about 4 phr or more, about 6 phr or more, or even about 8 phr or more. In embodiments, the amount of silica in the rubber formulation may be about 20 phr or less, about 18 phr or less, about 16 phr or less, about 14 phr or less, or even about 12 phr or less. In embodiments, the amount of silane in the rubber compound ranges from about 1 phr to about 20 phr, from about 1 phr to about 18 phr, from about 1 phr to about 16 phr, from about 1 phr to about 14 phr, from about 1 phr to about 12 phr, from about 2 phr to about 20 phr, from about 2 phr to about 18 phr, from about 2 phr to about 16 phr, from about 2 phr to about 14 phr, from about 2 phr to about 12 phr, from about 4 phr to about 20 phr, from about 4 phr to about 18 phr, from about 4 phr to about 16 ... from about 4 phr to about 12 phr, from about 6 phr to about 20 phr, from about 6 phr to about 18 phr, from about 6 phr to about 16 phr, from about 6 phr to about 14 phr, from about 6 phr to about 12 phr, from about 8 phr to about 20 phr, from about 8 phr to about 18 phr, from about 8 phr to about 16 phr, from about 8 phr to about 14 phr, or even from about 4 phr to about 12 phr, or any and all subranges formed from any of these endpoints.

[0067] In embodiments, the rubber compound may include additional rubbers that are not polymerized reaction products derived from vinylbenzocyclobutane. These additional rubbers may also include other synthetic rubbers, such as synthetic rubbers derived from petroleum-based feedstocks, synthetic rubbers derived from other sustainable processes, and natural rubber. As one skilled in the art will appreciate, natural rubber is synthesized by and obtained from plants. For example, natural rubber can be obtained from Hevea rubber trees, guayule shrub, gopher plant, mariola, rabbitbrush, milkweed, goldenrods, pale Indian plantain, rubber vine, Russian dandelions, mountain mint, American germander, and tall bellflower.

[0068] If used, other synthetic polymers may include, but are not limited to, synthetic polyisoprene, polybutadiene, polyisobutylene-co-isoprene, neoprene, poly(ethylene-co-propylene), poly(styrene-co-butadiene), poly(styrene-co-isoprene), poly(styrene-co-isoprene-co-butadiene), poly(isoprene-co-butadiene), poly(ethylene-co-propylene-co-diene), polysulfide rubbers, acrylic rubbers, urethane rubbers, silicone rubbers, epichlorohydrin rubbers, and mixtures thereof. These elastomers can have a myriad of macromolecular structures, including linear, branched, and star structures.

[0069] Generally, the rubber compositions of the present invention comprise from about 5 to about 45 weight percent, and in other embodiments from about 15 to about 40 weight percent, and in other embodiments from about 20 to about 35 weight percent of an elastomer, based on the total weight of the tire components.

[0070] In embodiments, the rubber formulation may be substantially free of curatives used in sulfur / zinc based crosslinking processes or peroxide based crosslinking processes. In embodiments, the rubber formulation may be substantially free of zinc oxide, sulfur, diphenyl guanidine, fatty acids, benzothiazoles, sulfenamides, sulfenimides, thiurams, dithiocarbamates, or combinations thereof. In one or more embodiments, the total weight percent of curatives in the rubber formulation may be less than about 1.0 weight percent, less than about 0.9 weight percent, less than about 0.8 weight percent, less than about 0.7 weight percent, less than about 0.6 weight percent, less than about 0.5 weight percent, less than about 0.3 weight percent, or even less than about 0.1 weight percent.

[0071] In one or more embodiments, the rubber compound may include at least one copper-containing compound, including acetates, acetylacetonates, aluminates, bicarbonates, borates, bromates, carbonates, chlorites, cyanides, diethylcitrates, halides, hexafluoroacetylacetonates, hexafluorophosphates, hexafluorosilicates, dihydrogenphosphates, hydrogencarbonates, hydrogensulfates, hydrogensulfides, hydrogensulfites, hydroxides, hypochlorites, iodates, nitrates, nitrites, oxalates, oxides, perfluorophthalocyanines, peroxides, phosphates, phthalocyanines, pyrophosphates, silicates, sulfamates, sulfates, sulfides, sulfites, tartrates, tetrafluoroborates, thiocyanates, thiolates, thiosulfates, tosylates, and triflates of these metals. Preferred compounds in this context include CuOCOCH3, Cu(OCOCH3)2, Cu(OCOCH3)2xH2O, Cu(C5H7O2)2, CuBr, CuBr2, CuCO3, CuCO3, Cu(OH)2, CuCl, CuCl2, CuCl2xH2O, Cu[C H3(CH2)3CH(C2H5)CO2]2, CuF2, CuF2xH2O, Cu(HCO2)2, Cu(HCO2)2xH2O, Cu(OH)2, Cu2(OH)PO4, CuI, CuFe2O4, Cu(NO3)2, Cu(NO3)2xH2O, Cu2O, CuO, Cu(C 32 H 16N8), Cu2P2O7xH2O, CuSO4, CuSO4xH2O, CuS, Cu[OCCH(OH)CH(OH)CO2]xH2O, Cu(BF4)2, Cu(BF4)xH2O, Cu(SCN), Cu(BF4)2, Cu(PF6)2, or CuF2. Particularly preferred compounds include Cu(BF4)2, Cu(PF6)2, or CuF2. Without being bound by theory, it is believed that these copper compounds can reduce the temperature required to cure the rubber compound by reducing the energy required for the VBCB in the statistical copolymer to form crosslinks.

[0072] Method of preparation In embodiments, the rubber compound of the present disclosure may be made by a process that includes polymerizing a conjugated diene monomer and a VBCB monomer, optionally a vinyl aromatic monomer, in the presence of an anionic initiator to produce polymer chains having living ends and randomized components to produce a statistical copolymer. The polymerization may produce a statistical copolymer as described above. The rubber compound may then be heated to a temperature of 170°C to 240°C. This heating of the rubber compound may cause the statistical copolymer to form crosslinks within the rubber compound.

[0073] In embodiments, an anionic initiator is used during polymerization of the statistical copolymer of the rubber compound. In embodiments, the anionic initiator may be a hydrocarbyl lithium compound. In embodiments, the anionic initiator may include ethyl lithium, n-propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, tert-octyl lithium, n-decyl lithium, phenyl lithium, 2-naphthyl lithium, 2-butyl-phenyl lithium, 4-phenyl-butyl lithium, cyclohexyl lithium, cyclopentyl lithium, the reaction product of diisopropyl benzene and butyl lithium, and combinations thereof. In embodiments, the anionic initiator may be n-butyl lithium.

[0074] In embodiments, the randomization component may be used during the synthesis of statistical copolymers of rubber compounds. Without being bound by theory, it is believed that the randomization component may affect the microstructure of the statistical copolymer, allowing for random distribution of monomer units of different compositions along the polymer chain.

[0075] In some embodiments, the randomization component includes those with oxygen or nitrogen heteroatoms and non-bonding electron pairs.Examples include linear and cyclic oligomeric oxolanyl alkanes; dialkyl ethers of mono- and oligoalkylene glycols (also known as glyme ethers); "crown" ethers; tertiary amines; linear THF oligomers; and the like.Linear and cyclic oligomeric oxolanyl alkanes are described in U.S. Patent Nos. 4,429,091 and 9,868,795, which are incorporated herein by reference. Specific examples of compounds useful as randomizers include 2,2-bis(2'-tetrahydrofuryl)propane, 1,2-dimethoxyethane, N,N,N',N'-tetramethylethylenediamine (TMEDA), tetrahydrofuran (THF), 1,2-dipiperidylethane, dipiperidylmethane, hexamethylphosphoramide, N-N'-dimethylpiperazine, diazabicyclooctane, dimethyl ether, diethyl ether, tri-n-butylamine, and mixtures thereof. In other embodiments, potassium alkoxides may be used to randomize the styrene distribution.

[0076] In embodiments, the method of making the rubber compound may include heating the rubber compound to a temperature of about 170° C. to about 240° C. In embodiments, the method may further include adding Cu(BF4)2 to the rubber compound prior to heating. In embodiments, the method of making the rubber compound may include heating the rubber compound to a temperature of about 170° C. or higher, about 180° C. or higher, about 190° C. or higher, or even about 200° C. or higher. In embodiments, the method of making the rubber compound may include heating the rubber compound to a temperature of about 240° C. or lower, about 230° C. or lower, about 220° C. or lower, or even about 210° C. or lower. In embodiments, the method of making the rubber compound may include heating the rubber compound to a temperature of about 170°C to about 240°C, about 170°C to about 230°C, about 170°C to about 220°C, about 170°C to about 210°C, about 180°C to about 240°C, about 180°C to about 230°C, about 180°C to about 220°C, about 180°C to about 210°C, about 190°C to about 240°C, about 190°C to about 230°C, about 190°C to about 220°C, about 190°C to about 210°C, about 200°C to about 240°C, about 200°C to about 230°C, about 200°C to about 220°C, or even about 200°C to about 210°C, or any and all subranges formed from any of these endpoints.

[0077] Rubber Compounds In embodiments, the rubber compound may have a maximum torque MH of about 19 dNm to about 30 dNm. In embodiments, the rubber compound may have a minimum torque ML of about 0.7 to about 0.8 dNm. In embodiments, the rubber compound may have a T90 time of about 50 minutes to about 70 minutes. In embodiments, the rubber compound may have a T50 time of about 10 minutes to about 15 minutes.

[0078] The rubber compounds disclosed herein may have a similar loss tangent tan δ at 0° C. compared to a control rubber compound, indicating similar wet traction performance. In embodiments, the rubber compounds may have a tan δ at 0° C. of 0.330 or greater.

[0079] The tan δ at 30° C. of a rubber composition is an indication of its dry traction when incorporated into a tire tread. In embodiments, the rubber compound may have a tan δ at 30° C. of 0.130 or greater.

[0080] The rubber compounds disclosed herein have a reduced loss tangent tan δ at 60° C. compared to a control rubber compound, which correlates with reduced rolling resistance. In embodiments, the rubber compounds may have a tan δ at 60° C. of 0.175 or less.

[0081] The rubber compounds disclosed herein have a reduced storage modulus G' at -20°C or -30°C compared to a control rubber compound, which correlates with increased traction on snow or ice. In embodiments, the rubber compounds may have a G' of 77 or less at -20°C. In embodiments, the rubber compounds may have a G' of 1565 or less at -30°C.

[0082] In embodiments, the rubber compound may have a change in storage modulus ΔG′ of about 8.4 to about 7.8 as measured in a strain sweep of 0.25% to 14% strain performed at 60° C. and 10 Hz.

[0083] In embodiments, the rubber compound may have a change in loss tangent tan δ of about 0.045 to 0.060 as measured in a strain sweep of 0.25% to 14% strain performed at 60° C. and 10 Hz.

[0084] In embodiments, the rubber compound may have a loss tangent tan δ at 5% strain of about 0.145 to about 0.155. In embodiments, the rubber compound may have a loss tangent tan δ at 10% strain of about 0.150 to about 0.170.

[0085] In embodiments, the rubber compound may have a modulus of elasticity at 200% strain M200 of about 6.3 MPa to about 10.2 MPa at room temperature. In embodiments, the rubber compound may have a modulus of elasticity at 200% strain M200 of about 2.8 MPa to about 5.2 MPa at 100°C. In embodiments, the rubber compound may have a modulus of elasticity at 100% strain M100 of about 11.1 MPa to about 15.4 MPa at room temperature. In embodiments, the rubber compound may have a modulus of elasticity at 100% strain M100 of about 5.0 MPa to about 6.6 MPa at 100°C. In embodiments, the rubber compound may have a modulus of elasticity at 50% strain M50 of about 1.75 MPa to about 7.7 MPa at room temperature. In embodiments, the rubber compound may have a modulus of elasticity at 50% strain M50 of about 1.6 to about 6.6 at 100°C.

[0086] In embodiments, the rubber compound may have a stress at break Tb of about 10.5 MPa to about 20 MPa at room temperature. In embodiments, the rubber compound may have a stress at break Tb of about 5 MPa to about 9 MPa at 100°C. In embodiments, the rubber compound may have an elongation at break Eb of about 105% to about 320% at room temperature. In embodiments, the rubber compound may have an elongation at break Eb of about 55% to about 180% at 100°C.

[0087] In embodiments, the rubber compound may have a % Tensile Strain at Tear of about 55% to about 165%. In embodiments, the rubber compound may have a toughness of about 1000 MPa to about 3900 MPa. In embodiments, the rubber compound may have a load per thickness of about 11.5 N / m to about 20 N / m.

[0088] In embodiments, the rubber compounds disclosed herein may have a % bound rubber similar to the % bound rubber of the control rubber compound.

[0089] In embodiments, the rubber compound may have a total swell percentage of from about 230% to about 300%.

[0090] In embodiments, the rubber compound may be used in tire treads. The rubber compounds of the present disclosure may also be utilized in other components and articles that utilize rubber compounds, such as tire sidewalls, inner tubes and tire innerliners, air cushions, pneumatic sprays, airbags, tire curing bladders, high temperature hoses and conveyor belts, damping mounts for engines, and the like.

[0091] In one or more embodiments, tires and / or other rubber-containing components and articles may include fiber reinforcements made by substituting non-petroleum materials for synthetic fibers. For example, mechanically recycled fibers, chemically recycled fibers, or bio-based fibers may be used. Similarly, tires may include metal reinforcements made from recycled steel and / or other round or sustainable metals. These non-petroleum fibers and recycled metals may be used exclusively in tires or in combination with conventional fiber and / or metal reinforcements. EXAMPLES

[0092] The rubber compounds described herein are further described in the following examples, which are not intended to limit the rubber compounds.

[0093] measurement Number average molecular weight (Mn), weight average molecular weight (Mw), and peak molecular weight (Mp) were determined by gel permeation chromatography using a TOSOH Esosec HLC-8320 GPC system and a TOSOH TSK gel GMHxl-BS column with THF as the solvent. The system was calibrated using a universal calibration with polystyrene standards and corrected using the Mark-Houwink constants for polybutadiene or poly(styrene-co-butadiene).

[0094] Vinylbenzocyclobutane content, vinyl content, and styrene content in d-chloroform at 25°C 1 Determined by 1 H nuclear magnetic resonance spectroscopy.

[0095] Glass transition temperature T g was measured by differential scanning calorimetry, which involved a starting temperature of 23° C., heating to 200° C. at a sweep rate of 10° C. / min, cooling to −120° C., and reheating to 200° C. at a sweep rate of 10° C. / min.

[0096] Tan δ at 0°C, 30°C, and 60°C, and G' at -20°C were measured using a temperature sweep test conducted with an Advanced Rheometric Expansion System (ARES) from TA Instruments. The test was conducted using a frequency of 3.14 rad / sec. The temperature started at -115°C and increased to 100°C.

[0097] Tensile mechanical properties such as modulus at 50% strain, modulus at 200% strain, stress at break Eb, and maximum strain Tb were determined following the guidelines of standard procedures described in ASTM D412 using dumbbell specimens, including but not limited to the above. The specimens were strained at a constant rate and the resulting force was recorded as a function of extension (strain). The force readouts were expressed as engineering stress, with reference to the original cross-sectional area of ​​the specimen. The specimens were tested at 28°C. The same mechanical tensile properties were also tested at 100°C. The maximum stress and maximum strain rates were also measured at both temperatures.

[0098] Example 1 - Synthesis of Vinylbenzocyclobutane Copolymer To an oven-dried and nitrogen-purged 800 mL bottle, 119.8 g of hexane, 35.3 g of a 34 wt% solution of styrene in hexane, 244.9 g of a 19.6 wt% solution of 1,3-butadiene in hexane, 0.09 mL of a 1.6 M solution of 2,2-ditetrahydrofurylpropane (80% meso isomer), and 0.25 mL of a 1.6 M solution of n-butyllithium in hexane were added. Various amounts of a 1 M solution of 4-vinylbenzocyclobutane (VBCB) in hexane were also added to produce polymers 1-3. The amount of 4-vinylbenzocyclobutane is shown in Table 1 for each reaction to produce comparative polymers A and B and polymers 1-3. After addition, the bottle was immersed in a 50°C water bath and stirred. After 2 hours, the polymer solution was removed from the water bath and quenched with 0.1 mL of isopropanol. The solution was coagulated in an excess of isopropanol containing butylated hydroxytoluene. The properties of the resulting polymer are shown in Table 2.

[0099] [Table 1]

[0100] [Table 2]

[0101] Example 2 - Formulation of Polymer with Carbon Black In Example 2, the polymers synthesized in Example 1 were compounded to form rubber compounds. The compound mixture formulations are shown in Tables 3 and 4 (in phr). Each rubber compound was prepared first in a master batch and then in a final batch. In the master batch, the comparative polymers in Table 2 were mixed with carbon black, zinc oxide, stearic acid, and oil, while Polymer 1, Polymer 2, and Polymer 3 were mixed with carbon black and oil.

[0102] The masterbatch portion of the compound was mixed in a 65g Banbury mixer operated by a cam rotor at 60 RPM and 133°C. The polymer was placed in the mixer first and after 30 minutes the remaining ingredients were added except for the stearic acid. For the comparative sample, the stearic acid was then added after 3 minutes. The masterbatch was mixed for a total of 5-6 minutes. At the end of mixing the temperature of the polymer was approximately 165°C. The masterbatch portion was then transferred to a mill operating at a temperature of 60°C, sheeted and then cooled to room temperature.

[0103] The final batch portions were mixed by adding the masterbatch and hardener materials to the mixer simultaneously for the comparative samples, whereas for the experimental samples, only the masterbatch was added to the mixer. The initial mixer temperature was 65°C, which was operated at 45 RPM. The final material was removed from the mixer 2.5 minutes after the material temperature reached 100°C-105°C. The final batch portions were then sheeted in a Dynastat button into 7.62 cm x 15.24 cm x 0.19 cm sheets. Comparative formulations C1 and C2 were cured in a standard mold placed in a hot press at 171°C for 30 minutes. Example formulations E1, E2, and E3 were cured at 220°C for 45 minutes.

[0104] [Table 3]

[0105] [Table 4]

[0106] Referring now to Table 5, Rubber Process Analyzer (RPA) results are shown as measured according to ASTM D5289 at 171° C. for the comparative compounds and 220° C. for the example compounds.

[0107] [Table 5]

[0108] As shown in Table 5, example formulations E1, E2, and E3 cured to crosslink densities equal to or greater than comparative formulations C1 and C2 without the use of accelerators or sulfur, as indicated by MH values ​​equal to or greater than E1, E2, and E3.

[0109] Referring now to Table 6, certain tensile properties are shown.

[0110] [Table 6]

[0111] As shown in Table 6, example compounds E2 and E3 have a higher modulus at both 200% and 50%, and a lower percent elongation at break at both 28° C. and 100° C. The higher modulus and lower elongation at break indicate that E2 and E3 had a higher crosslink density than comparative compounds C1 and C2, which is consistent with the data from the RPA testing in Table 5. Taken together, Tables 5 and 6 show that the properties of the cured rubber compounds can be controlled by controlling the amount of VBCB in the polymer.

[0112] Referring now to Table 7, the bound rubber content and swelling of the rubber compounds are shown. The bound rubber content test was used to determine the percent of polymer bound to the filler particles in each rubber composition. Bound rubber was measured by immersing a small specimen of the uncured raw material in a large excess of toluene for three days. The solvent extracted the soluble rubber from the sample. After three days, the excess toluene was drained and the sample was air-dried and then dried in an oven at approximately 100°C to constant weight. The remaining specimen forms a weak cohesive gel containing the filler and some of the original rubber. The amount of rubber remaining with the filler is the bound rubber. The bound rubber content is then calculated according to the following formula:

[0113]

number

[0114] Wd is the weight of the dry gel, F is the weight of the filler or solvent insoluble material in the gel (same as the weight of the filler in the original sample), and R is the weight of the polymer in the original sample. The percentage of bound rubber provides a means of measuring the interaction between the rubber (polymer) and the filler in the rubber composition, with a relatively high percentage of bound rubber indicating increased beneficial interaction between the rubber (polymer) and the filler. Swelling was measured according to ASTM D2765.

[0115] [Table 7]

[0116] As shown in Table 7, the comparative and example compounds showed similar percentages of bound rubber ±5%, indicating that the presence of VBCB did not interfere with the rubber-filler interaction in the rubber compound. Example compounds E2 and E3 had lower swelling percentages than comparative compounds C1 and C2, indicating that E2 and E3 had higher crosslink density than C1 or C2.

[0117] Example 3 - Polymer and Silica Blend In Example 3, six polymers were synthesized using the same procedure as in the synthesis of Example 1, except for polymer 5, where 2.4 mL of 1M 4-vinylbenzocyclobutane (VBCB) in hexane was added after the addition of butadiene. After 2 hours of polymerization, an additional 0.4 mL of 1M 4-vinylbenzocyclobutane (VBCB) in hexane was added and the bottle was returned to the 50° C. bottle bath for 30 minutes. The solution was then quenched with 0.1 mL of isopropanol. The solution was coagulated in an excess of isopropanol containing butylated hydroxytoluene. The polymer properties were recorded in Table 8. The polymers were then compounded into rubber formulations. The compound mixture formulations are shown in Tables 9, 10, 10a, and 11 (in phr). Each rubber formulation was prepared first in a master batch and then in a final batch.

[0118] [Table 8]

[0119] The masterbatch portion of the compound was mixed in a 65g Banbury mixer operated by a cam rotor at 60 RPM and 133°C. The polymer was placed in the mixer first and after 30 minutes the remaining ingredients except for the stearic acid were added. The masterbatch was mixed for a total of 5-6 minutes. At the end of mixing the temperature of the rubber samples was approximately 165°C. The masterbatch portion was then transferred to a mill operating at a temperature of 60°C, sheeted and then cooled to room temperature.

[0120] The first remill portion was mixed by adding the masterbatch and additional silica, silane, resin, and AO. For the comparative sample, the stearic acid was then added after 3 minutes. The remill was mixed for a total of 4-5 minutes. At the end of mixing, the temperature of the rubber sample was approximately 165°C. The remill portion was then transferred to a mill operating at a temperature of 60°C, sheeted, and then cooled to room temperature.

[0121] The second remill portion was mixed by adding the first remill portion to a 65g Banbury mixer operated by a cam rotor at 45 RPM and 133°C. The second remill portion was mixed for a total of 4-5 minutes. At the end of mixing, the temperature of the rubber samples was approximately 165°C. The second remill portion was then transferred to a mill operating at a temperature of 60°C, sheeted, and then cooled to room temperature.

[0122] The final batch portions were mixed by adding the second remill portion and the curative material to the mixer simultaneously for the comparative samples, whereas for the experimental samples, only the second remill was added to the mixer. The initial mixer temperature was 65°C, which was operated at 45 RPM. The final material was removed from the mixer 2.5 minutes after the material temperature reached 100°C-105°C. The final batch portions were then sheeted in a Dynastat button into 7.62 cm x 15.24 cm x 0.19 cm sheets. Comparative formulation C3 was cured in a standard mold placed in a hot press at 171°C for 30 minutes. Example formulations E4, E5, E6, E7 and E8 were cured at 220°C for 45 minutes.

[0123] [Table 9]

[0124] [Table 10]

[0125] [Table 11]

[0126] [Table 12]

[0127] Referring now to Table 12, certain tensile properties of the rubber compounds are shown.

[0128] [Table 13]

[0129] As shown in Table 12, Example Compounds E4-E8 had higher modulus and lower percent elongation at break at both 100% and 50%. The higher modulus and lower elongation at break indicate that E4-E8 had higher crosslink density than Comparative Compound C3. Furthermore, Example Compound E5, which has a VBCB monomer unit located at the end of the polymer chain, has a higher percent elongation at break compared to the other Example Compounds, which is closer to the elongation at break of Comparative Compound C3.

[0130] Example 4 - Use of a catalyst to accelerate cure In Example 4, the effect of catalyst on the cure of polymers containing VBCB monomer was investigated. The polymers were synthesized according to the procedure in Example 1, and the properties of the synthesized polymer (Polymer 9) are shown in Table 13. 0.78 phr of Cu(BF4)2 was added to a portion of the polymer without catalyst and with catalyst, then cured at 200°C to investigate the effect of this addition on the cure of the polymer. Testing was performed on an Alpha Technologies RPA at 0.1% strain and 10 Hz.

[0131] [Table 14]

[0132] As shown in FIG. 1, the addition of Cu(BF4)2 to the polymer caused it to cure more rapidly and more strongly at 200°C compared to the polymer without the addition of Cu(BF4)2, indicating that the presence of Cu(BF4)2 effectively catalyzes the cure of the polymer containing VBCB.

[0133] Embodiments of the present invention include, but are not limited to, the following. 1. A rubber compound comprising a statistical copolymer comprising a polymerized crosslinkable reaction product derived from a conjugated diene monomer and vinyl benzocyclobutane, the rubber compound being substantially free of conventional rubber curatives. 2. Conventional rubber curatives include sulfur and peroxides in any of the rubber compounds described in the preceding paragraphs. 3. A rubber compound according to any preceding paragraph, wherein the curative comprises zinc oxide, sulfur, diphenyl guanidine, fatty acid, benzothiazole, sulfenamide, sulfenimide, thiuram, dithiocarbamate, or combinations thereof. 4. A rubber compound according to any preceding paragraph, wherein the rubber component of the rubber compound comprises from about 20 phr to about 100 phr of the statistical copolymer, based on the total weight of the rubber component. 5. The rubber compound of any preceding clause, wherein the conjugated diene monomer is selected from the group consisting of 1,3-butadiene, isoprene, 1,3-pentadiene, 1,3-hexadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 2-methyl-1,3-pentadiene, 3-methyl-1,3-pentadiene, 4-methyl-1,3-pentadiene, 2,4-hexadiene, 1,3-cyclopentadiene, 1,3-cyclohexadiene, 1,3-cycloheptadiene, 1,3-cyclooctadiene, and combinations thereof. 6. A rubber compound according to any preceding paragraph, wherein the statistical copolymer comprises the polymerized crosslinkable reaction product derived from a conjugated diene monomer, a vinyl benzocyclobutane, and a vinyl aromatic monomer. 7. The rubber compound of any preceding clause, wherein the vinyl aromatic monomer is selected from the group consisting of styrene, alpha-methylstyrene, p-methylstyrene, o-methylstyrene, p-butylstyrene, vinylnaphthalene, p-tertbutylstyrene, 4-vinylbiphenyl, 2-vinylnaphthalene, 9-vinylanthracene, vinylcatechol, and combinations thereof. 8. A rubber compound according to any preceding paragraph, wherein the conjugated diene monomer is 1,3-butadiene and the vinyl aromatic monomer is styrene. 9. A rubber compound according to any preceding paragraph, wherein the rubber compound further comprises from about 5 to about 75 phr of carbon black. 10. A rubber compound according to any preceding paragraph, wherein the rubber compound further comprises from about 1 phr to about 70 phr of oil. 11. A rubber compound according to any preceding paragraph, wherein the rubber compound further comprises from about 1 phr to about 150 phr of silica. 12. A rubber compound according to any preceding paragraph, wherein the rubber compound further comprises from about 1 phr to about 20 phr of a silane. 13. Rubber compounds include CuOCOCH3, Cu(OCOCH3)2, Cu(OCOCH3)2xH2O, Cu(C5H7O2)2, CuBr, CuBr2, CuCO3, CuCO3, Cu(OH)2, CuCl, CuCl2, CuCl2xH2O, Cu[CH3(CH 2)3CH(C2H5)CO2]2, CuF2, CuF2xH2O, Cu(HCO2)2, Cu(HCO2)2xH2O, Cu(OH)2, Cu2(OH)PO4, CuI, CuFe2O4, Cu(NO3)2, Cu(NO3)2xH2O, Cu2O, CuO, Cu(C 32 H 16 N8), Cu2P2O7xH2O, CuSO4, CuSO4xH2O, CuS, Cu[O2CCH(OH)CH(OH)CO2]xH2O, Cu(BF4)2, Cu(BF4)xH2O, Cu(SCN), Cu(BF4)2, Cu(PF6)2, CuF2, or combinations thereof. 14. The rubber compound of any preceding clause, wherein the rubber compound further comprises Cu(BF4)2, Cu(PF6)2, CuF-2, or a combination thereof. 15. The rubber compound of any preceding clause, wherein the rubber compound further comprises styrene-butadiene rubber, butadiene rubber, butyl rubber, EPDM, natural rubber, polyisoprene, or a combination thereof, wherein the styrene-butadiene rubber and butadiene rubber do not comprise polymerized reaction products derived from vinylbenzocyclobutane. 16. A rubber compound according to any preceding clause, wherein the rubber compound is cured by heating the rubber compound to a temperature of 200°C or greater. 17. A statistical copolymer has a molecular weight of about 1.0 x 10 5 A rubber compound as described in any preceding clause having a weight average molecular weight of 0.1 g / mol or more. 18. The rubber compound of any preceding clause, wherein the statistical copolymer comprises from about 0.02% by weight to about 2% by weight of vinylbenzocyclobutane, based on the total weight of the statistical copolymer. 19. A rubber compound according to any preceding clause, wherein the statistical copolymer comprises from 1 to 15 vinylbenzocyclobutane monomer units per chain of the statistical copolymer. 20. The rubber compound of any preceding paragraph, wherein the statistical copolymer comprises from about 50% by weight to about 99% by weight of a conjugated diene monomer, based on the total weight of the statistical copolymer. 21. A rubber compound according to any preceding paragraph, wherein the statistical copolymer comprises from about 5% by weight to about 50% by weight of vinyl aromatic monomer, based on the total weight of the statistical copolymer. 22. A rubber compound according to any preceding paragraph, wherein the statistical copolymer has at least one vinylbenzocyclobutane monomer unit at the end of the copolymer chain. 23. A tire tread comprising a rubber compound according to any preceding paragraph. 24. A method of making a rubber compound according to any preceding paragraph, the method comprising heating the rubber compound to a temperature of about 170°C to about 240°C, wherein heating the rubber compound causes the statistical copolymer to form crosslinks within the rubber compound. 25. The method of any preceding clause, further comprising adding one or more compounds, including Cu(BF4)2, Cu(PF6)2, CuF-2, to the rubber compound prior to heating. 26. The method of any preceding clause, wherein the anionic initiator comprises ethyllithium, n-propyllithium, isopropyllithium, n-butyllithium, sec-butyllithium, tert-octyllithium, n-decyllithium, phenyllithium, 2-naphthyllithium, 2-butyl-phenyllithium, 4-phenyl-butyllithium, cyclohexyllithium, cyclopentyllithium, the reaction product of diisopropylbenzene and butyllithium, and combinations thereof. 27. The method of any preceding clause, wherein the anionic initiator is n-butyllithium. 28. The method of any preceding clause, wherein the randomizing component comprises 2,2-ditetrahydrofurylpropane, meso-2,2-ditetrahydrofurylpropane, dimethoxybenzene, tetrahydrofuran, dimethoxyethane, diethylene glycol dibutyl ether, diethylene glycol dimethyl ether, triethylamine, pyridine, N-methylmorpholine, N,N,N',N'-tetramethylethylenediamine, 1,2-dipiperidinoethane, potassium t-amylate, potassium t-butoxide, sodium t-amylate, or a combination thereof. 29. A tire component comprising a cured rubber matrix with a filler dispersed therein, the cured rubber matrix comprising greater than 40%, or 50%, or 60%, or 70%, or 80%, or 90%, or 99% by weight of a statistical copolymer comprising a polymerized crosslinkable reaction product derived from conjugated diene monomers and vinyl benzocyclobutane, and one or more additional components dispersed within the cured rubber matrix, wherein one or more of these components are sustainable materials. 30. A tire component as described in any preceding clause wherein additional sustainable materials include recycled carbon black. 31. A tire component as described in any preceding paragraph, wherein additional sustainable materials include rice husk ash derived silica, and pyrolytic carbon black. 32. A tire component as described in any preceding paragraph, wherein the tire component includes a sustainable oil dispersed within the rubber matrix as described above. 33. A tire component comprising any of the preceding paragraphs, wherein the tire component is comprised within a tire, the tire comprising more than 40% by weight, or 50% by weight, or 60% by weight, or 70% by weight, or 80% by weight, or 90% by weight, or 99% by weight of sustainable materials. 34. A tire as described in any preceding clause, wherein the tire contains recycled metals.

[0134] It will be apparent that modifications and variations are possible without departing from the scope of the present disclosure, as defined in the appended claims. More specifically, although certain aspects of the present disclosure are identified herein as preferred or particularly advantageous, it is contemplated that the present disclosure is not necessarily limited to those aspects.

[0135] Claims

Claims

1. 1. A rubber compound comprising: a statistical copolymer comprising a polymerized crosslinkable reaction product derived from conjugated diene monomers and vinylbenzocyclobutane; A rubber compound, wherein the rubber compound is substantially free of conventional rubber curatives.

2. The conventional rubber curing agent is 10. The rubber compound of claim 1, comprising sulfur and a peroxide.

3. 10. The rubber compound of claim 1, wherein the curative comprises zinc oxide, sulfur, diphenyl guanidine, a fatty acid, a benzothiazole, a sulfenamide, a sulfenimide, a thiuram, a dithiocarbamate, or a combination thereof.

4. The rubber compound of any one of claims 1 to 3, wherein the rubber component of the rubber compound comprises from about 20 phr to about 100 phr of the statistical copolymer, based on the total weight of the rubber component.

5. The rubber compound according to any one of claims 1 to 3, wherein the conjugated diene monomer is selected from the group consisting of 1,3-butadiene, isoprene, 1,3-pentadiene, 1,3-hexadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 2-methyl-1,3-pentadiene, 3-methyl-1,3-pentadiene, 4-methyl-1,3-pentadiene, 2,4-hexadiene, 1,3-cyclopentadiene, 1,3-cyclohexadiene, 1,3-cycloheptadiene, 1,3-cyclooctadiene, and combinations thereof.

6. 4. The rubber compound according to any one of claims 1 to 3, wherein said statistical copolymer comprises a polymerized crosslinkable reaction product derived from said conjugated diene monomer, said vinyl benzocyclobutane, and a vinyl aromatic monomer, said vinyl aromatic monomer being selected from the group consisting of styrene, alpha-methylstyrene, p-methylstyrene, o-methylstyrene, p-butylstyrene, vinylnaphthalene, p-tertbutylstyrene, 4-vinylbiphenyl, 2-vinylnaphthalene, 9-vinylanthracene, vinylcatechol, and combinations thereof.

7. The rubber compound is from about 5 to about 75 phr of carbon black; from about 1 phr to about 70 phr of oil; about 1 phr to about 150 phr of silica; The rubber compound of any one of claims 1 to 3, further comprising from about 1 phr to about 20 phr of a silane.

8. A method for making a rubber compound according to any one of claims 1 to 3, said method comprising the steps of: heating the rubber compound to a temperature of about 170° C. to about 240° C.; The method of claim 1, wherein the statistical copolymer forms crosslinks within the rubber compound by heating the rubber compound.

9. Before heating, Cu(BF 4 ) 2 , Cu(PF 6 ) 2 , CuF- 2 9. The method of claim 8, further comprising adding to the rubber compound one or more compounds comprising:

10. A tire component comprising:

1. A tire component comprising a cured rubber matrix having a filler dispersed therein, said cured rubber matrix comprising greater than 40%, or 50%, or 60%, or 70%, or 80%, or 90%, or 99% by weight of a statistical copolymer comprising a polymerized crosslinkable reaction product derived from a conjugated diene monomer and vinyl benzocyclobutane, and one or more additional components dispersed within said cured rubber matrix, wherein one or more of these components are sustainable materials.

Citation Information

Patent Citations

  • Olefinic benzocyclobutene polymer and its production

    JP1987148503A

  • Conjugated polymer products, methods of making and compositions

    JP2020510111A

  • Conjugated polymer products, methods of making and compositions

    JP2021507018A

Cited By

  • Rubber composition for extruded hoses, and hoses

    JP7850331B1